EORTC consensus recommendations for the treatment of mycosis fungoides/Sézary syndrome: update 2023: review - Latzka, Johanna; Assaf, Chalid; Bagot, Martine; Cozzio, Antonio; Dummer, Reinhard; Guenova, Emmanuella; Gniadecki, Robert; Hodak, Emmilia; Jonak, Constanze; Klemke, Claus-Detlev; Knobler, Robert; Morrris, Stephen; et al. (European journal of cancer, 2023)
On behalf of the EORTC Cutaneous Lymphoma Tumours Group (EORTC-CLTG) and following up on earlier versions published in 2006 and 2017 this document provides an updated standard for the treatment of mycosis fungoides and Sézary syndrome (MF/SS). It considers recent relevant publications and treatment options introduced into clinical practice after 2017. Consensus was established among the authors through a series of consecutive consultations in writing and a round of discussion. Treatment options are assigned to each disease stage and, whenever possible and clinically useful, separated into first- and second line options annotated with levels of evidence. Major changes to the previous version include the incorporation of chlormethine, brentuximab vedotin, and mogamulizumab, recommendations on the use of pegylated interferon α (after withdrawal of recombinant unpegylated interferons), and the addition of paragraphs on supportive therapy and on the care of older patients. Still, skin-directed therapies are the most appropriate option for early-stage MF and most patients have a normal life expectancy but may suffer morbidity and impaired quality of life. In advanced disease treatment options have expanded recently. Most patients receive multiple consecutive therapies with treatments often having a relatively short duration of response. For those patients prognosis is still poor and only for a highly selected subset long term remission can be achieved with allogeneic stem cell transplantation. Understanding of the disease, its epidemiology and clinical course, and its most appropriate management are gradually advancing, and there is well-founded hope that this will lead to further improvements in the care of patients with MF/SS.